Влияние органической связки на свойства гранулята и керамики на основе нитрида алюминия; Известия вузов. Физика; Т. 58, № 6 (2) - Дитц А. А. Александр Андреевич; Ревва И. Б. Инна Борисовна; Погребенков В. М. Валерий Матвеевич; Косолапов А. А. Артем Анатольевич; Орехов А. С. Александр Сергеевич (2015, 2015)
Заглавие с экрана